The Effectiveness of E-Learning Implementation Using Social Learning Network Schoology on Motivation & Learning Achievement - JW.Nugroho Joshua; I Putu Agus Swastika; Ni Made Estiyanti (Prodi Pendidikan Teknik Informatika Universitas Pendidikan Ganesha, 2016)
The advancement of technology and the openness of the internet access in many places in Indonesia, making the shift in styles of learning and acquiring knowledge. Significant growth on such access also has changed the way everyone connected, communicate with each other and develop a social community. Unlike previous generations, college students in today’s era found many learning resources, both from his tutor at the College as well as from fellow students, also from other learning sources outside his College. The fact of this openness requires a new approach for a lecturer in the College to adopt a way of delivering his teaching, so the learning objectives can be achieved. One such implementation is implementing e-learning using the Social Learning Network. The purpose of this study is to see to what extent the effectiveness of the e-learning implementation on motivation and learning achievements of students. The research results showed that the learning opportunities has the greatest role in the motivation of learning, followed by collaborative learning. A high learning motivation using Social Learning Network, Schoology became a highly influential variable on learning achievements of Students in STMIK Primakara Bali